Great Gunfighters of the West - Breihan, Carl W. (San Antonio, Texas The Naylor Company, 1962)
An account of killers, both good men and bad men, that is as exciting as it is factual.
Wild Bill Hickok. -- Wild Bill Longley. -- Cullen Baker. -- Bat Masterson. -- Henry Starr. -- Henry Brown. -- Ben Thompson. -- Clay Allison. -- Frank Leslie.
Keywords: Biography -- West (U.S.) -- Juvenile literature; Crime -- West (U.S.) -- Juvenile literature; Criminals -- West (U.S.) -- Juvenile literature; Crime; Criminals; United States -- West